Fe-S Proteins Acting as Redox Switch: New Key Actors of Cellular Adaptive Responses - Golinelli-Cohen, Marie-Pierre; Bouton, Cecile (Current Chemical Biology, 2017)
Abstract: Background: Iron-sulfur clusters are inorganic prosthetic groups composed of only iron and inorganic sulfur atoms. Organisms develop different pathways to sense their local environment and to respond and adapt to changes. Objective: We focused on Fe-S-containing proteins, which control their activity in response to redox signals by changing the redox state of their cluster. Result: When reduced, these Fe-S cluster-containing sensors are all inactive. As soon as their cluster perceives a signal that induces its oxidation, they switch to an « active state ». Conclusion: This sensing mechanism efficiently helps cells to turn on survival pathways quickly and recover from stressful conditions.
Keywords: redox state